Envisioning an ecological systems theoretical approach to sexual and reproductive health programs in Greenland - Peterson, Malory; Reimer, Gitte Adler; Rink, Elizabeth (Grønlandsk Kultur- og Samfundsforskning, 2024)
People in Greenland experience disparate sexual and reproductive health (SRH) outcomes relative to populations in other circumpolar countries and Denmark. SRH in Greenland is intrinsically linked to multiple levels of an individual’s life, including family, partner relationship, healthcare access, and unique sociocultural factors. In this article we advocate for the use of ecological systems theory to design SRH programs in Greenland that incorporate the many interrelated systems that affect individual health outcomes. We introduce key concepts and strengths of ecological systems models for SRH programs, and we elucidate specific constructs of ecological systems theory that complement the existing Greenlandic health environment. We suggest that ecological systems theory is culturally congruent with how people in Greenland understand the interconnectedness of individuals, families, communities, and the natural and built environment. Incorporating ecological systems theory in SRH program design may promote interorganizational collaboration of SRH services, and integrate SRH education across family, school, and healthcare settings.